Lycium barbarum polysaccharide protects human keratinocytes against UVB-induced photo-damage. (1st February 2017) - Li, Huaping; Li, Zhenjie; Peng, Liqian; Jiang, Na; Liu, Qing; Zhang, Erting; Liang, Bihua; Li, Runxiang; Zhu, Huilan
Abstract: Ultraviolet B (UVB) irradiation plays a key role in skin damage, which induces oxidative and inflammatory damages, thereby causing photoaging or photocarcinogenesis. Lycium barbarum polysaccharide (LBP), the most biologically active fraction of wolfberry, possesses significant antioxidative and anti-inflammatory effects on multiple tissues. In the present study, the photoprotective effects and potential underlying molecular mechanisms of LBP against UVB-induced photo-damage were investigated in immortalized human keratinocytes (HaCaT cells). The data indicated that pretreatment with LBP significantly attenuated UVB-induced decrease in cell viability, increase in ROS production and DNA damage. LBP also significantly suppressed UVB-induced p38 MAPK activation, and subsequently reversed caspase-3 activation and MMP-9 expression. Notably, LBP was found to induce Nrf2 nuclear translocation and increase the expression of Nrf2-dependent ARE target genes. Furthermore, the protective effects of LBP were abolished by siRNA-mediated Nrf2 silencing. These results showed that the antioxidant LBP could partially protect against UVB irradiation-induced photo-damage through activation of Nrf2/ARE pathway, thereby scavenging ROS and reducing DNA damage, and subsequently suppressing UVB-induced p38 MAP pathway. Thus, LBP can be potentially used for skincare against oxidative damage from environmental insults.